Analysis of Total Polar Material in Selected Indian Snack’s Fried Oil - Kumar, R.; Bhattacharya, B.; Agarwal, T.; Chakkaravarthi, S. (Journal of Scientific Research, 2021)
The study was envisaged to examine the quality of frying oil used by street food vendors for two of the most popular food items viz. Samosa and Jalebi in India. Changes in the quality of frying oil were analysed by analysing the total polar material (TPM) content in the oil using an oil tester and Attenuated total reflectance–Fourier transform infrared (ATR-FTIR) spectroscopy. Total 143 oil samples were collected at different frying times, i.e. 0, 2 and 4 h from five different Samosa and Jalebi vendors. In both the fried food oil samples, TPM content increased with increasing frying time. The TPM content in the 4 h fried oil samples of Jalebi was significantly (p< 0.001) higher than the samosa fried oil. Partial Least Square Regression (PLS) model based on the 1st derivative FTIR spectra exhibited good prediction capability for TPM values with a high regression coefficient (R2 ≥ 0.99) and low root mean square error (RMSE).